Investigating Rotor Conditions on Wind Turbines Using Integrating Tree Classifiers. (9th June 2022) - Saha, Bikash Chandra; Dhanraj, Joshuva Arockia; Sujatha, M.; Vallikannu, R.; Alanazi, Mohana; Almadhor, Ahmad; Sathyamurthy, Ravishankar; Erko, Kuma Gowwomsa; Sugumaran, V.
Abstract : Renewable wind power is productive and feasible to manage the energy crisis and global warming. The wind turbine's blades are the essential components. The dimension of wind turbine blades has been increased with blade sizes varying from approx. 25 m up to approx. 100 m or even greater with a specific purpose to increase energy efficiency. While wind turbine blades tend to be highly stressed by environmental conditions, the wind turbine blade must be constantly tested, inspected, and monitored for wind turbine blades safety monitoring. This research presents a methodology adaptation on machine learning technique for appropriate classification of different failure conditions on blade during turbine operation. Five defects were reported for the diagnosis study of defective wind turbine rotor blades, and the considered defects are blade crack, erosion, loose hub blade contact, angle twist, and blade bend. The statistical features have been drawn from the recorded vibration signals, and the important features was selected through J48 classifier. Eight tree-dependent classifiers were used to categorize the state of the rotor blades. Among the classifiers, the least absolute deviation tree performed better with the classification percentage of 90% (Kappa statistics = 0.88, MAE = 0.0362, and RMSE = 0.1704 ) with a computational time of 0.06 s.